2011
DOI: 10.1097/ijg.0b013e31820bd1ce
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Term Safety and Efficacy of Transscleral Cyclophotocoagulation After Tube Shunt Failure

Abstract: Purpose To determine the efficacy and safety of diode transscleral cyclophotocoagulation (TSCPC) after tube shunt failure. Patients and Methods The patient population consisted of 32 eyes of 31 patients with uncontrolled glaucoma. Each eye had a previously implanted aqueous tube shunt and was currently on maximally tolerated medication. Each eye also underwent TSCPC treatment using the Iridex (Mountain View, CA) diode laser with a maximum of 360 degrees of treatment. All 31 charts were reviewed for data pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…1823 Among patients who failed initial tube shunt surgery in the TVT Study, the cumulative probability of success was 57% at 4 years with repeat glaucoma surgery. This result is similar to the rates reported in previous studies (Table 7), including success rates of 37% to 86% for second tube shunts 2429 and 67% to 71% for cyclodestruction 2931 in patients who failed tube shunt implantation.…”
Section: Discussionsupporting
confidence: 92%
“…1823 Among patients who failed initial tube shunt surgery in the TVT Study, the cumulative probability of success was 57% at 4 years with repeat glaucoma surgery. This result is similar to the rates reported in previous studies (Table 7), including success rates of 37% to 86% for second tube shunts 2429 and 67% to 71% for cyclodestruction 2931 in patients who failed tube shunt implantation.…”
Section: Discussionsupporting
confidence: 92%
“…CPC significantly reduced IOP and mean number of glaucoma medications 16 . Later studies by Panarelli et al 17 and Ness et al 18 also found transscleral CPC to be an effective treatment following shunt failure.…”
Section: Discussionmentioning
confidence: 95%
“…16 TSCPC has a significant ocular hypotensive effect on glaucoma refractory to both tube shunt and medical therapy. 17 An unqualified success after cycloablation would be the attainment of a target IOP without the need for further medication, coupled with preservation of visual function. CycloDiode therapy appears to be effective in lowering IOP, in both the short and long term.…”
Section: Methods and Considerationsmentioning
confidence: 99%
“…Glaucoma following penetrating keratoplasty, which has an incidence ranging from 10-52%, often proves refractory to medical treatment.1-3 We introduce a case of refractory post-PKP glaucoma in order to demonstrate the efficacy of ECP in treating post-PKP glaucoma and to describe its potential delayed effect in achieving intraocular pressure control Diode Laser Transscleral Cyclophotocoagulation as Primary Surgical Treatment for Medically Uncontrolled Chronic Angle Closure Glaucoma Long-Term Clinical Outcomes. 17 Endoscopic cyclophotocoagulation (ECP) was introduced as an alternative to trans-scleral cyclophotocoagulation for treating refractory glaucomas in order to minimise complications such as phthisis and hypotony by providing direct visualisation of the ciliary processes. Glaucoma following penetrating keratoplasty, which has an incidence ranging from 10-52%, often proves refractory to medical treatment.…”
Section: Methods and Considerationsmentioning
confidence: 99%